Vaccination against SARS-CoV-2 in rheumatic diseases: Safety issues - B. S. Belov; A. M. Lila; E. L. Nasonov (Научно-практическая ревматология, 2022)
The problem of coronavirus disease 2019 (Coronavirus diseases, COVID-19) two years later still remains relevant both socially and medically. As one of the methods of combating the current COVID-19 pandemic, most experts rely on the widespread use of vaccination. However, the use of vaccines against SARS-CoV-2 in patients with rheumatic diseases (RD) raises a number of issues related to the effectiveness, immunogenicity, and safety of immunization, including leveling the risks of exacerbation of the underlying disease or the development of new autoimmune phenomena. For this reason it is very important to analyze data on the above-mentioned aspects in real time, especially given that patients of the rheumatology circle were excluded from the clinical development programs of vaccines against SARS-CoV-2. This review presents the results of last year’s research on the safety of vaccination against COVID-19 in patients with RS. A brief description of the main anticovedic vaccines is given. Post-vaccination adverse events were quite frequent after the first, second or both doses of vaccines in patients with RS, which is consistent with the data obtained in the general population. In general, the frequency of exacerbation of RD after vaccination against COVID-19 seems to be quite low (5–7%) and has no significant associations with a specific vaccine or anti-rheumatic therapy. At the same time, unambiguous interpretation of these data is difficult for at least three reasons: a) in many studies, only the symptoms developing after the first dose of the vaccine were taken into account; b) the time-limited post-vaccination follow-up period; c) significant discrepancies in the interpretation of exacerbations of the disease. Within the framework of the problem under consideration, there are still a lot of questions, the answers to which should be obtained in large prospective controlled studies.